Retinopathy of Prematurity—A Brief Review - Saba Al Rashaed (Dr. Sulaiman Al Habib Medical Journal)
Retinopathy of Prematurity (ROP) is a proliferative retinal vascular disease affecting the retina of premature infants and is considered the major cause of blindness in children and the most common cause of retinal vasculopathy in premature and in low-birth-weight infants. The clinical spectrum of ROP varies from spontaneous regression to bilateral retinal detachment and total blindness. Between these two extremes lies the form of ROP, which mandates treatment with laser photocoagulation, or surgery. Increasing rates of preterm births together with better survival rates but lack of efficient screening and delays in the diagnosis causes an increase in the ROP rate. In developing countries, the atypical form of aggressive posterior ROP was reported in the use of unblended oxygen of more mature infants. Prevention of ROP by following efficient protocols of supplemental oxygen, prevention of sepsis, timely screening, and laser treatment requiring coordinated teamwork between neonatologists and trained ophthalmologists are mandatory to prevent ROP.